PERAN IBU RUMAH TANGGA DALAM MEMBANTU PEREKONOMIAN KELUARGA - Mery Afrina; Nurhamlin " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2014)
This thesis was submitted in order to be eligible undergraduate sociology degree. With the title “The Role of Housewife In Helping Economy of Family In Garuda Permai Housing Phase 1 Tampan District of Pekanbaru City". The problem addressed in this paper was to describe how the role of the housewife in helping the family economy In Garuda Permai Housing Phase 1 Tampan District of Pekanbaru City. The role of housewife was seen from indicators such as : how the respondents' profile work, how respondent worked to help the family economy and how the role of the respondents worked in performing the function of the family. Respondents were housewives who work; the sample used the census technique which collected data as a whole by means of direct interviews using questionnaires. The method used descriptive quantitative methods of data analysis and descriptive explanation. Screening instrument data used were observation, questionnaires and interviews as well as tables of data contained in the table. The theory was used to issue the role of the housewife 's work was the theory of the role of Paul B.Horton and Chester L.Hunt, the theory of family functions of Horton and Hunt and gender theory of Fakih.The results of research in general conducted it could be said that housewife helped the family economy due to economic factors and education effort for getting a permanent job, so most of the respondents work in a way to trade. With the decision of the respondents worked in the household had an average wife who took over as the husband was able to share a few more decisions by the wifeKeyword: House Wife, Family Economy, Family Function